Implementation of Feeder System to Support Monitoring the Potential Malnutrition - Swastina, Liliana; Riadi, Akhmad Selamet (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
The case of malnutrition affecting many toddlers of Banjarmasin in isolated areas, remote areas, and remote villages. It is caused by the resultant of economic problems, facilities, infrastructures, and the lack of medical personnel. One of the ways undertaken by the government to overcome this problem is to carry out Posyandu activities. The posyandu program is organized to improve and monitor the nutrition of children under five. However, the reporting of posyandu data by each puskesmas is sometimes delayed because of the large amount of bureaucracy that must be passed to get to the center. Therefore a system feeder application is needed to monitor and mapping on the number of toddlers with potential malnutrition in the city of Banjarmasin.